Application of Diversion for Children in conflict with the Law: How is the Criminal Justice system - Yuli Indarsih (Institute Of computer Science (IOCS), 2019)
Child law issues have many dynamics and challenges that are contrary to the constitution and human rights, but in the process, criminal acts involving minors have their own way of solving them and one of them is through diversion or protection based on values and rights . In addition to lightening the legal settlement process, diversion also avoids a process that will have a very bad impact on children's development, through diversion it is also hoped that the justice system that is very burdensome to children can be immediately changed and replaced with a process that is very burdensome. It is deliberative, more humane and far from acts of violence that will give a bad stigma to the image of Indonesia's judiciary, this study uses a qualitative method approach by examining several literature studies related to the research objectives, namely to find out how diversion is applied. for children related to law and how the justice system is for the Indonesian people.